Identificación de Aglutininas Febriles en Crías de Camélidos Sudamericanos Alpacas. - Andrango Alulema, Edison Xavier (2017)
This project was carried out at Cotopaxi Province, Pujilí Canton, Zumbahua Parish in the community of Apahua. The objective was to identify febrile agglutinins in South American camelids (alpacas), this was done to detect antibodies in the animal's serum. Twenty-six pups were selected from 3 weeks to 7 months old, including females and males, determining the study group, enumerated and identified by handling, sampling and removal to the laboratory. The research showed the presence of antibodies in the sample of the individuals, finding that in 26 cases, 85% are positive to infections caused by Salmonella paratyphi flagellar species, 81% correspond to S. typhi flagellar, And 50% to Salmonella somatic paratyphi, demonstrating an agglutination of 1: 160, and it was demonstrated that there are no positive cases for the genus Brucella, and its species, except for one subject, giving positive to Brucella abortus which was analyzed by The competitive Elisa test where the result was negative, being able to affirm that the majority of infections in pups of alpacas is due only to microorganisms of the genus Salmonella.